Benign hereditary chorea: phenotype, prognosis, therapeutic outcome and long term follow-up in a large series with new mutations in the TITF1/NKX2-1 gene. Issue 10 (24th July 2012) - Gras, Domitille; Jonard, Laurence; Roze, Emmanuel; Chantot-Bastaraud, Sandra; Koht, Jeanette; Motte, Jacques; Rodriguez, Diana; Louha, Malek; Caubel, Isabelle; Kemlin, Isabelle; Lion-François, Laurence; Goizet, Cyril; et al.
Abstract : Background: Benign hereditary chorea (BHC) is a rare autosomal dominant disorder characterised by childhood onset that tends to improve in adulthood. The associated gene, NKX2-1 (previously called TITF1 ), is essential for organogenesis of the basal ganglia, thyroid and lungs. The aim of the study was to refine the movement disorders phenotype. We also studied disease course and response to therapy in a large series of genetically proven patients. Methods: We analysed clinical, genetic findings and follow-up data in 28 NKX2-1 mutated BHC patients from 13 families. Results: All patients had private mutations, including seven new mutations, three previously reported mutations and three sporadic deletions encompassing the NKX2-1 gene. Hypotonia and chorea were present in early infancy, with delayed walking ability (25/28); dystonia, myoclonus and tics were often associated. Attention deficit hyperactivity disorder (ADHD) was present in seven. Among the 14 patients followed-up until adulthood, nine had persistent mild chorea, two had near total resolution of chorea but persistent disabling prominent myoclonus and three recovered completely. Learning difficulties were observed in 20/28 patients, and three had mental retardation. Various combinations of BHC, thyroid (67%) and lung (46%) features were noted. We found no genotype–phenotype correlation. A rapid and sustained beneficial effect on chorea was obtained in 5/8 patients treated with tetrabenazine. Conclusion: Early onset chorea preceded by hypotonia is suggestive of BHC. Associated thyroid or respiratory disorders further support the diagnosis and call for genetic studies. Tetrabenazine may be an interesting option to treat disabling chorea.